(untitled) (Global Journal of Science Frontier Research, 2020)
Lightning discharges are formed during the development of a thunderstorm cell. First of all, it should be said that thunderclouds consist of several thunderstorm cells closely adjacent to each other, the development of processes in which is identical, but shifted in time. By cell we mean a region with a certain extent in the horizontal direction, in which all the basic processes take place. It is the physical processes that occur in such cells that lead to the occurrence of lightning.